Pengembangan Kampung Wisata Sewu Kembang Berbasis Ekonomi Hijau di Nglurah, Kelurahan Tawangmangu, Kabupaten Karanganyar - Didik Setyawan; Dian Kresnadipayana; Dionysius Andang Arifwibawa; Faiz Rahman Siddiq; Bagus Ismail Adhi Wicaksana (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of tourism villages based on local wisdom is an important community empowerment strategy to promote green economic self-reliance. Tourism villages serve not only as tourist destinations but also as platforms for sustainable rural economic empowerment. Sewu Kembang Tourism Village in Nglurah Hamlet possesses significant natural and cultural potential; however, this potential has not been optimally managed in terms of production systems, institutional management, and marketing. This community service program aims to enhance compost fertilizer production capacity, strengthen institutional management, and develop digital-based marketing strategies for the Joint Business Group (KUBE) “Dwi Tunggal” and the Tourism Awareness Group (Pokdarwis) of Nglurah Hamlet. The program employed a participatory approach through workshops, technical assistance, and operational document facilitation. The results indicate improvements in production capacity, the establishment of structured management systems, and the implementation of marketing media and strategies. These findings demonstrate that empowerment based on local wisdom and green economy principles can enhance institutional capacity and support the sustainable economic development of tourism villages.